2019
DOI: 10.3390/catal9121013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Steam Reforming of Acetic Acid as a Model Compound of the Aqueous Fraction of Microalgae HTL Using Co-M/SBA-15 (M: Cu, Ag, Ce, Cr) Catalysts

Abstract: Hydrogen production derived from thermochemical processing of biomass is becoming an interesting alternative to conventional routes using fossil fuels. In this sense, steam reforming of the aqueous fraction of microalgae hydrothermal liquefaction (HTL) is a promising option for renewable hydrogen production. Since the HTL aqueous fraction is a complex mixture, acetic acid has been chosen as model compound. This work studies the modification of Co/SBA-15 catalyst incorporating a second metal leading to Co-M/SBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 85 publications
2
24
0
Order By: Relevance
“…Garcia et al [34] reported the beneficial effect of Cr addition to Co based catalysts, as a promoter towards hydrogenation-dehydrogenation reactions (i.e., coke precursors hydrogenation). Chromium was also shown to be a textural promoter, reducing the crystallite dimensions and limiting the sintering of the active species [35]; moreover, chromium promoter was shown to better improve the steam reforming activity of rare earth based catalyst compared to other metals [30,36]. Our previous work [37] highlighted the good performance of a Co-Cr/SBA-15 catalyst in terms of high activity, hydrogen yield and low coke deposition.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Garcia et al [34] reported the beneficial effect of Cr addition to Co based catalysts, as a promoter towards hydrogenation-dehydrogenation reactions (i.e., coke precursors hydrogenation). Chromium was also shown to be a textural promoter, reducing the crystallite dimensions and limiting the sintering of the active species [35]; moreover, chromium promoter was shown to better improve the steam reforming activity of rare earth based catalyst compared to other metals [30,36]. Our previous work [37] highlighted the good performance of a Co-Cr/SBA-15 catalyst in terms of high activity, hydrogen yield and low coke deposition.…”
Section: Introductionmentioning
confidence: 78%
“…Co and Co/Cr catalysts, supported over mesostructured SBA-15 material, were prepared through the incipient wetness impregnation and co-precipitation method using Co(NO 3 ) 2 •6H 2 O and Cr(NO 3 ) 3 •9H 2 O as precursor salts (purchased by Sigma-Aldrich, St. Louis, MO, USA), as described elsewhere [30]. The SBA-15, used as the support, was syn-thetized according the hydrothermal method described for the first time by Zhao [31].…”
Section: Preparation and Characterization Of The Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co and Co-Cr catalysts, supported over mesostructured SBA-15 material, were prepared through the incipient wetness impregnation and co-precipitation method using Co(NO3)2•6H2O and Cr(NO3)3•9H2O as precursor salts, as described elsewhere [30]. The SBA-15, used as the support, was synthetized according the hydrothermal method described for the first time by Zhao [31].…”
Section: Preparation and Characterization Of The Catalystsmentioning
confidence: 99%
“…Thus, the performance of different supports, capable of enhancing hydrogen yield and deactivation resistance, has been investigated [29]. SBA-15, instead of common amorphous silica, was reported to be a very useful support, capable of preventing Co particles aggregation and metal sintering [30]. SBA-15, a well ordered hexagonal mesoporous (4-12 nm) silica structure presents several attractive characteristics as a catalytic support, such as high specific surface area (600-1000 m 2 g -1 ), ease of synthesis, high thermal and mechanical stability [31][32][33].…”
Section: Introductionmentioning
confidence: 99%